2018
DOI: 10.1002/ncp.10196
|View full text |Cite
|
Sign up to set email alerts
|

Admission 25‐Hydroxyvitamin D Levels Are Associated With Functional Status at Time of Discharge from Intensive Care Unit in Critically Ill Surgical Patients

Abstract: Background: Vitamin D status is associated with length of stay (LOS) and discharge destination in critically ill patients. To further understand this relationship, we investigated whether admission 25-hydroxyvitaminD (25OHD) levels are associated with discharge functional status in the intensive care unit (ICU). Methods: In this retrospective study, data from 2 surgical ICUs at a large teaching hospital were analyzed. 25OHD levels were measured within 24 hours of ICU admission and Functional Status Score for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 96 publications
(113 reference statements)
0
6
0
Order By: Relevance
“…D status was associated with prolong poor functional status at time of discharge from intensive care unit in critical ill surgical patients. 89 Perioperatively, the evidence from in vivo studies have shown that low level of 25(OH)D was associated with delay wound healing, longer emergence time and increased risk of postoperative cognitive impairment. 69,90,91 Clinically, preoperative vitamin D status in patients undergoing non-cardiac surgery was associated with infectious complication and respiratory complication related to general anesthesia.…”
Section: Vitamin D Air Pollution and Effects On Organ Transplantationmentioning
confidence: 99%
See 1 more Smart Citation
“…D status was associated with prolong poor functional status at time of discharge from intensive care unit in critical ill surgical patients. 89 Perioperatively, the evidence from in vivo studies have shown that low level of 25(OH)D was associated with delay wound healing, longer emergence time and increased risk of postoperative cognitive impairment. 69,90,91 Clinically, preoperative vitamin D status in patients undergoing non-cardiac surgery was associated with infectious complication and respiratory complication related to general anesthesia.…”
Section: Vitamin D Air Pollution and Effects On Organ Transplantationmentioning
confidence: 99%
“…The studies in critically‐ill patients had found that vitamin D insufficiency was associated with risks of respiratory infection, sepsis, respiratory and kidney failure, increased time of ventilator, intensive care unit (ICU) stay, and mortality 71,74,76,88 . Furthermore, low vitamin D status was associated with prolong poor functional status at time of discharge from intensive care unit in critical ill surgical patients 89 …”
Section: Introductionmentioning
confidence: 99%
“…Pre-clinical data suggest that not only is vitamin D a potent anti-inflammatory agent, 10 but that it is essential for epithelial cell growth and differentiation, 11 expression of endogenous antimicrobial peptides at barrier (e.g., skin, gut, lungs) sites, 12 and promoting optimal platelet function. 13 Observational studies by members of our group suggest that vitamin D status is associated with duration of mechanical ventilation, 14 functional status at ICU discharge, 15 disposition after acute care hospitalization, 16 and mortality in critically ill patients. 17 High-dose vitamin D supplementation has even been shown by members of our group 18 and others 19 to improve clinical outcomes in critically ill patients with low baseline 25-hydroxyvitamin D (25OHD) levels.…”
Section: Introductionmentioning
confidence: 99%
“…Brook and others in a recent issue of our journal reported that admission 25‐hydroxy vitamin D (25OHD) level in critically ill patients was associated with discharge functional status score. Higher scores implying better functional status were associated with higher initial 25OHD levels.…”
mentioning
confidence: 99%